A case report on severe combined immune deficiency: A rare inherited pediatric disorder (Indian Journal of Case Reports, 2020)
Severe combined immune deficiency (SCID), also known as alymphocytosis, Glanzmann-Rinker syndrome, and thymic alymphoplasia, is characterized by impairment in the differentiation of T, B lymphocytes, and natural killer cells. Adenosine deaminase deficiency is the most common cause of SCID, as it leads to dysfunction of T, B lymphocytes and severe lymphopenia. Due to the severity of the disease, early diagnosis is essential to provide desired treatment and get a good therapeutic outcome. They need special treatment to strengthen the immune system and improve the chance of survival such as hematopoietic stem cell transplantation and enzyme replacement therapy (ERT). We present the case of a 4-month baby, born to a consanguineous couple with altered vitals and symptoms pertaining to immunodeficiency, and were on empirical antibiotic therapy and supportive care therapy to control opportunistic infections and stabilize the patient. This case report gives a brief insight into SCID.